2019
DOI: 10.1111/sltb.12606
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Past Parenting and Adult Attachment as Vulnerability Factors for Suicidal Ideation in the Context of the Integrated Motivational–Volitional Model of Suicidal Behavior

Abstract: Objective We aimed to investigate whether perceptions of past parenting and current attachment orientations are associated with key components of the Integrated Motivational–Volitional (IMV) Model of Suicidal Behavior. We investigated the relationship between perceptions of past parenting, attachment, suicide ideation, defeat, entrapment, coping, and resilience. Method A total of 730 adult participants responded to an online questionnaire comprised of psychological measures. An initial regression analysis indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 69 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…They are likely to have concerns about losing or being abandoned by others (Hazan & Shaver, 1987). In addition to experiencing difficulties in their close relationships, those with an insecure pattern of attachment have been shown to exhibit other negative outcomes in adulthood, such as social anxiety, depression, addiction, suicidal ideation, eating disorders, and other physical and psychological maladies (Liu & Ma, 2019; Manning et al, 2017; Monteleone et al, 2018; Picardi et al, 2019; Zortea, Gray, & O'Connor, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They are likely to have concerns about losing or being abandoned by others (Hazan & Shaver, 1987). In addition to experiencing difficulties in their close relationships, those with an insecure pattern of attachment have been shown to exhibit other negative outcomes in adulthood, such as social anxiety, depression, addiction, suicidal ideation, eating disorders, and other physical and psychological maladies (Liu & Ma, 2019; Manning et al, 2017; Monteleone et al, 2018; Picardi et al, 2019; Zortea, Gray, & O'Connor, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous literature (Gandhi et al, 2016;Santens et al, 2018) and attachment theory (Bowlby, 1969(Bowlby, , 1973, we found that adolescents with higher levels of paternal and maternal attachment insecurity were more likely to report lifetime and current self-harm thoughts, and lifetime self-harm behaviours. Given the association between attachment insecurity and both lifetime self-harm thoughts and behaviours, and current self-harm thoughts, our findings also offer partial support for attachment insecurity as a pre-motivational variable within the IMV model , where parent-child attachment relationships may increase vulnerability for self-harm thoughts and behaviours (Zortea et al, 2019). Conversely, self-harm may influence attachment relationships (Ferrey et al, 2015), and this should be investigated in future studies.…”
Section: Confirmatory Analysesmentioning
confidence: 59%
“…However, contemporary 'ideation-toaction' theoretical models of suicidal behaviour distinguish between the psychosocial processes associated with self-harm thoughts, and those associated with self-harm behaviours (Klonsky & May, 2015;O'Connor, 2011;O'Connor & Kirtley, 2018). To this end, the current study builds upon recent research (Zortea et al, 2019) highlighting the utility of the Integrated Motivational-Volitional model for understanding how attachment is related to self-harm thoughts and behaviours. Within the IMV, attachment is posited as a pre-motivational factor, associated with both thoughts and behaviours (Zortea et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, in a cross-section study in Chinese adolescents, entrapment was proved to be signi cantly related with suicidal ideation and factors like thwarted belongingness and perceived burdensomeness could reinforce the relationship [21]. Furthermore, it has been repetitiously proved that entrapment mediated the relationship between defeat and suicidal ideation, with resilience as a possible alleviating factor [22,23]. Nevertheless, though many previous studies have dug into the entrapment-suicidal ideation relationship, few of them focus on medical students, the group of population at higher risk of suicide [24].…”
Section: Introductionmentioning
confidence: 99%